Unambiguous identification and characterization of a long‐term human metabolite of dehydrochloromethyltestosterone. Issue 8 (24th April 2018) - Forsdahl, Guro; Geisendorfer, Thomas; Göschl, Lorenz; Pfeffer, Sandra; Gärtner, Peter; Thevis, Mario; Gmeiner, Günter
Abstract: In doping control analysis, the characterization of urinary steroid metabolites is of high interest for a targeted and long‐term detection of prohibited anabolic androgenic steroids (AAS). In this work, the structure of a long‐term metabolite of dehydrochloromethyltestosterone (DHCMT) was elucidated. Altogether, 8 possible metabolites with a 17α‐methyl‐17β‐hydroxymethyl – structures were synthesized and compared to a major DHCMT long‐term metabolite detected in reference urine excretion samples. The confirmed structure of the metabolite was 4α‐chloro‐18‐nor‐17β‐hydroxymethyl‐17α‐methyl‐5α‐androst‐13‐en‐3α‐ol. Abstract : The structure of a long‐term metabolite of dehydrochloromethyltestosterone (DHCMT) was elucidated. Eight potential metabolites were synthesized and compared to a long‐term metabolite detected in reference urine samples. The long‐term metabolite was identified as 4α‐chloro‐18‐nor‐17β‐hydroxymethyl‐17α‐methyl‐5α‐androst‐13‐en‐3α‐ol.